Jeersannidhi Award Lecture- ENTOMOGENOUS FUNGI IN INDIA AND MANAGEMENT OF INSECT PESTS - AGARWAL, G. P. (Indian Phytopathology, 2002)
I feel honoured and express grateful thanks to the Executive Council of Indian Phytopathological Society for inviting me to deliver the Jeersannidhi Lecture for 1990. I have chosen to talk on ’Entomogenous fungi in India and management of insect pests,’ a subject in which I have been recently interested and 00 which topic Prof. M. J. Narasimhan delivered his inspiring Presidential Address to this Indian PhytopathologicalSociety two decades back.